Welcome to the ICD‐10 code for sarcopenia. Issue 5 (17th October 2016) - Anker, Stefan D.; Morley, John E.; von Haehling, Stephan
Abstract: The new ICD‐10‐CM (M62.84) code for sarcopenia represents a major step forward in recognizing sarcopenia as a disease. This should lead to an increase in availability of diagnostic tools and the enthusiasm for pharmacological companies to develop drugs for sarcopenia.